Maternal outcome in thyroid dysfunction - K., Manju V.; K., Sathiamma P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thyroid hormone status in pregnancy is an important predictor of pregnancy outcome regarding both the mother and fetus. Objective was study the maternal outcome in antenatal women presenting with thyroid dysfunction. Methods: This descriptive study was done in 449 pregnant ladies who attended Obstetrics and Gynecology Department Government TD Medical College, Alappuzha, Kerala, India during the period January 2014 to June 2015. Aim was studying the maternal outcome in those diagnosed to have thyroid dysfunction evidenced by abnormal thyroid function tests (TFT) done in each trimester. Results: Majority had subclinical hypothyroidism (SCH). Common complications were preeclampsia spontaneous abortion, anemia and recurrent pregnancy loss. Infertility, post-partum hemorrhage and abruption were significantly high in overt hypothyroidism. Anemia was significantly high in subclinical hypothyroidism. Conclusions: It is important to screen all pregnant women for thyroid dysfunction during first antenatal visit itself to facilitate early diagnosis and treatment and also can counsel regarding the adverse pregnancy outcome.